2018
DOI: 10.1155/2018/3964926
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Adiabatic Temperature Rise Test and Temperature Stress Simulation of Rock-Fill Concrete

Abstract: In the present study, we investigate the effect of the adiabatic temperature rise property of rock-fill concrete (RFC) on the temperature stress and crack resistance of RFC gravity dams. We conducted tests on the adiabatic temperature rise of RFC with a rock-fill ratio of 42%, 49%, and 55%, respectively. Based on the regression analysis of the test data, a calculation model of the adiabatic temperature rise, considering the rock-fill ratio, is developed, and the finite element analysis software ANSYS is employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Because of the effect of fly ash, the adiabatic temperature rise curve of CSG material still increased slightly at 18th days and remained stable until 24th days. Compared with [12], it can be seen that the hydration reaction rate of CSG material is slower and the reaction time is longer. e relationship between different cementing agent content and the final value of adiabatic temperature rise is presented in Figure 5.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 95%
See 1 more Smart Citation
“…Because of the effect of fly ash, the adiabatic temperature rise curve of CSG material still increased slightly at 18th days and remained stable until 24th days. Compared with [12], it can be seen that the hydration reaction rate of CSG material is slower and the reaction time is longer. e relationship between different cementing agent content and the final value of adiabatic temperature rise is presented in Figure 5.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 95%
“…ere is a considerable amount of literature about extensive thermal performance tests and temperature control crack prevention on ordinary concrete [6][7][8][9], RCC [10,11], rockfill concrete [12], and other materials. e investigations for the CSG materials are mainly focused on the relevant mechanical properties [13][14][15][16][17], while the impact of adiabatic temperature rise on the CSG material is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some discrete element numerical simulation research [14][15][16] has been carried out for the study of pouring compactness. In terms of material properties, the standard test methods for conventional concrete are not suitable for RFC; therefore, some well-designed experiments have been developed to determine the various physical properties of RFC, including static and dynamic compressive strength, tensile strength, elastic modulus, fracture energy, density, adiabatic thermal rise, frost and seepage resistance, creep, and interface behaviors [8,10,[17][18][19][20][21]. However, there is currently no relevant research focusing on the dynamic performance of RFC or comparing it to the alternatives, making it difficult to evaluate the difference in performance in comparison with CVC dams during earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that, the principal stresses and the horizontal displacements were increased if the reservoir length is extended. Zhang et al [14] studied the effect of the heat of hydration on rock-fill concrete, the study indicated that, without any temperature control, construction efficiency was improved where the occurrence of cracking was prevented and, as such, the construction cost was reduced. Kuzmanovic et al [15] developed a 3D numerical model to evaluate thermal stress in RCC dams.…”
Section: Introductionmentioning
confidence: 99%